Big data and understanding change in the context of planning transport systems. (April 2019) - Milne, Dave; Watling, David
Abstract: This paper considers the implications of so-called 'big data' for the analysis, modelling and planning of transport systems. The primary conceptual focus is on the needs of the practical context of medium-term planning and decision-making, from which perspective the paper seeks to achieve three goals: (i) to try to identify what is truly 'special' about big data; (ii) to provoke debate on the future relationship between transport planning and big data; and (iii) to try to identify promising themes for research and application. Differences in the information that can be derived from the data compared to more traditional surveys are discussed, and the respects in which they may impact on the role of models in supporting transport planning and decision-making are identified. It is argued that, over time, changes to the nature of data may lead to significant differences in both modelling approaches and in the expectations placed upon them. Furthermore, it is suggested that the potential widespread availability of data to commercial actors and travellers will affect the performance of the transport systems themselves, which might be expected to have knock-on effects for planning functions. We conclude by proposing a series of research challenges that we believe need to be addressed and warn against adaptations based on minimising change from the status quo.